(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Building Information Modeling (BIM) has profoundly altered the construction industry, prompting an increased focus on integrating BIM into academic curricula related to construction disciplines. Nevertheless, limited research has explored the global trends surrounding the integration of BIM within construction education. This study uses bibliometric analysis to identify and critically assess the prominent topics and trends in BIM education research over the last decade. Drawing from 462 bibliometric records from the Scopus database, the analysis utilized VOSviewer to visualize and assess patterns in co-authorship, co-word, and co-citation. The results indicate that the United States, China, and the United Kingdom have made the most significant strides in BIM education research, with strong collaborative ties observed between geographically proximate countries, such as China-Malaysia and USA-Brazil. The analysis of keyword co-occurrences suggests that BIM educational research is predominantly concentrated in civil engineering, construction management, and architecture. Furthermore, there is a discernable shift from traditional, discipline-specific teaching approaches towards interdisciplinary, collaborative, and problem-based learning paradigms incorporating advanced virtual technologies. Key emerging themes, such as “virtual reality,” “digital twins,” and “virtual learning environments,” underscore the evolving nature of BIM education. The study emphasizes the necessity of sustained advancements in BIM education, with particular emphasis on interdisciplinary collaboration, technological integration, and pedagogical innovation to meet the dynamic demands of the construction industry.